Driver drowsiness detection and alert mobile application (DDDA) / Nor Izzat Noor Zaimi - Noor Zaimi, Nor Izzat (2020)
Nowadays, road accidents are becoming common in the country. This might be due to microsleep which causes driver to fall asleep for a short period of time while driving. In this split second, the driver may lose control of the vehicle and cause an accident. This project aims to develop an application that can help driver to wake up in case the driver falls into microsleep. Moreover, this project will help driver to stay awake and focus while driving through the sound alert system. This application will use the driver’s face to detect the microsleep and then give an alert if microsleep is detected. The system is expected to help driver to stay awake and focus while driving.